Post-Construction Support and Sustainability in Community-Managed Rural Water Supply : Case Studies in Peru, Bolivia, and Ghana - Bakalian, Alexander; Wakeman, Wendy (Washington, DC, 2014)
This volume reports the main findings from a multi-country research project that was designed to develop a better understanding of how rural water supply systems are performing in developing countries. The author began the research in 2004 to investigate how the provision of support to communities after the construction of a rural water supply project affected project performance in the medium term. The author collected information from households, village water committees, focus groups of village residents, system operators, and key informants in 400 rural communities in Bolivia, Ghana, and Peru; in total, the author discussed community water supply issues with approximately 10,000 individuals in these communities. To the surprise, the author found the great majority of the village water systems were performing well. The findings on the factors influencing their sustainability will be of use to policy makers, investors, and managers in rural water supply.